Service Quality Strategy In Increasing Customer Satisfaction At Ice Bakery Tanjung Redeb Berau Regency - Syamsul Hadi; R. Satato; Mariane Novarista Wawo (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Ice bakery is a bakery located in the city of Berau. Ice Bakery is one of the shops that produces bread and cake every day. This research is a way to know, discuss, analyze, and conclude about service quality strategies in increasing customer satisfaction at Tanjung Redeb Ice Bakery, Berau Regency. Service quality is the level of service related to meeting consumer expectations and needs. Customer satisfaction is the consumer's response to the evaluation of the perceived mismatch between previous expectations and perceived product performance. This research was conducted with descriptive qualitative research. Data collection techniques using interviews, inteviews and theoretical data. Researchers used respondents as many as 11 people with the following details 1 Manager, 1 Barista, 1 SPG, 1 Cashier, 1 Head of Production, 1 Table Staff and 5 Customers at Ice Bakery Berau.